Pre-wedding Photography Practices of Prospective Brides and Grooms at Ullah Studio Palu in the Review of Islamic Law Sociology and Maqashid Al-Syariah - Sri Wahyuni Amin; Malarangan, Hilal; Sitti Musyahidah; Iskandar, Iskandar (State Islamic University Datokarama Palu, 2025)
The media plays a significant role in influencing various aspects of society, including the increasingly popular practice of pre-wedding photography. In Islam, until a valid marriage contract (akad) is conducted, couples remain non-mahram and are required to observe religious boundaries. This study aims to examine pre-wedding photography practices at Ullah Studio from the perspective of Islamic legal sociology. A qualitative approach was applied using literature studies and textual, contextual, and inter-contextual data analysis. The results show that pre-wedding photography at this studio adheres to Islamic ethics and legal principles, with no physical contact or interactions that violate religious norms. Pre-wedding photography is considered an acceptable cultural practice as long as it remains within the boundaries of Islamic teachings.